RDA element sets and RDA value vocabularies: Vocabularies for resource description in the semantic web - Assumpção, Fabrício Silva [UNESP]; Segundo, José Eduardo Santarem [UNESP]; Santos, Plácida Leopoldina Ventura Amorim da Costa [UNESP] (Springer Nature, 2015)
Considering the need for metadata standards suitable for the Semantic Web, this paper describes the RDA Element Sets and the RDA Value Vocabularies that were created from attributes and relationships defined in Resource Description and Access (RDA). First, we present the vocabularies included in RDA Element Sets: the vocabularies of classes, of properties and of properties unconstrained by FRBR entities; and then we present the RDA Value Vocabularies, which are under development. As a conclusion, we highlight that these vocabularies can be used to meet the needs of different contexts due to the unconstrained properties and to the independence of the vocabularies of properties from the vocabularies of values and vice versa.
Keywords: Functional Requirements for Bibliographic Records (FRBR); Resource Description and Access (RDA); Resource Description Framework (RDF); Vocabularies